2014
DOI: 10.1212/wnl.0000000000000367
|View full text |Cite
|
Sign up to set email alerts
|

Chronic meralgia paresthetica and neurectomy

Abstract: Objective: To understand the pathologic and clinical correlates of patients with chronic meralgia paresthetica (MP) undergoing lateral femoral cutaneous nerve (LFCN) neurectomy.Methods: A retrospective cohort approach was utilized to identify 7 patients undergoing LFCN neurectomy for intractable pain. Control autopsied LFCN was obtained. Clinical, radiologic, and electrophysiologic features were reviewed.Results: In identified cases, preoperative symptoms included severe lateral thigh pain and numbness. The du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
24
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 13 publications
3
24
0
1
Order By: Relevance
“…At human nerve compression sites, a thickened perineurium, subperineurial edema, Renaut bodies, nerve enlargement due to an increase in endoneurial connective tissue, marked decrease in large fibers, and an increase in thin myelinated fibers have been reported . Our pathologic findings were very similar to those made at peripheral nerve compression sites.…”
Section: Discussionsupporting
confidence: 86%
“…At human nerve compression sites, a thickened perineurium, subperineurial edema, Renaut bodies, nerve enlargement due to an increase in endoneurial connective tissue, marked decrease in large fibers, and an increase in thin myelinated fibers have been reported . Our pathologic findings were very similar to those made at peripheral nerve compression sites.…”
Section: Discussionsupporting
confidence: 86%
“…Important thereby to realize is that the lateral femoral nerve is a pure sensory nerve (contrary to most other entrapped nerves) and that, although neurectomy causes numbness of the anterolateral part of the thigh, we have found that most patients are not bothered by this numbness (de Ruiter et al, 2012). In addition, histopathologic analysis of resected nerve segments in patients with persistent symptoms of meralgia paresthetica has shown that several intraneural changes have occurred (Berini et al, 2014), which might explain why neurolysis sometimes fails to relieve symptoms.…”
mentioning
confidence: 70%
“…Imaging studies, including ultrasound and magnetic resonance neurography (MRN), may be useful, but further confirmatory studies are needed, plus MRN is not widely available. Although LFCN pathology in chronic meralgia paresthetica has been reported to show selective loss of large myelinated fibers, a functional study has suggested small‐fiber involvement . Similar to NCS, skin biopsy can differentiate sensory neuropathy from radiculopathy, as IENFD can be affected in sensory neuropathy but should not be affected by preganglionic root lesions.…”
Section: Discussionmentioning
confidence: 99%